2003
DOI: 10.1046/j.1432-1033.2003.03529.x
|View full text |Cite
|
Sign up to set email alerts
|

H2O2, but not menadione, provokes a decrease in the ATP and an increase in the inosine levels in Saccharomyces cerevisiae

Abstract: When Saccharomyces cerevisiae cells, grown in galactose, glucose or mannose, were treated with 1.5 mM hydrogen peroxide (H 2 O 2 ) for 30 min, an important decrease in the ATP, and a less extensive decrease in the GTP, CTP, UTP and ADP-ribose levels was estimated. Concomitantly a net increase in the inosine levels was observed. Treatment with 83 mM menadione promoted the appearance of a compound similar to adenosine but no appreciable changes in the nucleotide content of yeast cells, grown either in glucose or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…1A shows that LP cells of C.g.BG14 (wt) can resist up to 0.2 mM menadione and that this resistance is dependent on Cta1. Menadione is a cytotoxic quinone that generates superoxide and it has been shown that exposure to menadione induces the expression of S.c. and S.p.Cta1 (Nakagawa et al 1995, Osorio et al 2003. This result suggests that the superoxide generated by menadione is dismutated to H 2 O 2 , which is then reduced by the catalase.…”
Section: Discussionmentioning
confidence: 95%
“…1A shows that LP cells of C.g.BG14 (wt) can resist up to 0.2 mM menadione and that this resistance is dependent on Cta1. Menadione is a cytotoxic quinone that generates superoxide and it has been shown that exposure to menadione induces the expression of S.c. and S.p.Cta1 (Nakagawa et al 1995, Osorio et al 2003. This result suggests that the superoxide generated by menadione is dismutated to H 2 O 2 , which is then reduced by the catalase.…”
Section: Discussionmentioning
confidence: 95%
“…These data strongly suggest that the ability of tCid1 to incorporate uridylyl residues instead of adenylyl residues is specific to this polymerase. We next determined whether UTP could still out-compete ATP at physiologically relevant ratios, given that ATP is present in a 2-to 10-fold molar excess over UTP in vivo (3,31). tCid1 was incubated with (A) 15 and ATP in a 10-fold molar excess over UTP or with the combination of UTP, CTP, and GTP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7D slow or fast branch on right is determined by the occupancy of NBD1 with ATP, which in turn depends on the levels of ATP and ADP as well as on the nucleotide state of NBD2. Under normal growth conditions, the ATP concentration in the yeast cytosol is in the low millimolar range whereas the ADP level is ϳ5-10 times lower (40). The concentration of ADP is relevant because ADP is a competitive inhibitor (41) and thus increases the apparent K m for ATP.…”
Section: Discussionmentioning
confidence: 99%